2018
DOI: 10.1111/oik.04766
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch between dietary requirements for lipid by a predator and availability of lipid in prey

Abstract: Growth is an important factor in predicting an organism's overall success as an adult. Understanding how abiotic and biotic factors influence body size is key to predicting how environmental changes will impact organisms and predicting optimal behaviors under varying conditions. Food items can vary widely in nutrient content and this variation can affect growth. We tested how the quantity and macronutrient content of live prey affected the growth of juvenile jumping spiders, Phiddipus audax, using 420 spiderli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 48 publications
1
32
4
1
Order By: Relevance
“…In such circumstances, fitness and growth may be directly impacted by a deficit of carbohydrates and fats, as well as metabolic penalties associated with the energetic and toxicity costs of metabolizing amino acids (Solon-Biet et al, 2014;Piper et al, 2017;Raubenheimer and Simpson, 2019). Such dietary imbalance is frequently encountered in the wild, not only by herbivores (e.g., Rothman et al, 2011;Cui et al, 2018) and omnivores (Remonti et al, 2016), including humans (Speth and Spielmann, 1983), but also carnivores (Wilder et al, 2013;Jensen et al, 2014;Kohl et al, 2015;Wiggins and Wilder, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such circumstances, fitness and growth may be directly impacted by a deficit of carbohydrates and fats, as well as metabolic penalties associated with the energetic and toxicity costs of metabolizing amino acids (Solon-Biet et al, 2014;Piper et al, 2017;Raubenheimer and Simpson, 2019). Such dietary imbalance is frequently encountered in the wild, not only by herbivores (e.g., Rothman et al, 2011;Cui et al, 2018) and omnivores (Remonti et al, 2016), including humans (Speth and Spielmann, 1983), but also carnivores (Wilder et al, 2013;Jensen et al, 2014;Kohl et al, 2015;Wiggins and Wilder, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Protein is essential to animal nutrition, providing the building blocks for new tissue, enzymes, etc., and it is therefore unsurprising that animals in their natural environment commonly favor N-rich diets (Mattson, 1980). In many cases, however, consumers may be constrained to diets that are richer in protein relative to carbohydrate and lipid than is optimal (Rothman et al, 2011;Jensen et al, 2014;Nyffeler et al, 2016;Remonti et al, 2016;Wiggins and Wilder, 2018). Animals must then use protein as a source of energy, potentially leading to the onset of toxicity via deamination and release of ammonia and incurring various energetic and other costs associated with metabolic transformations, synthesis of reduced forms of N and excretion (Bender, 2012;Piper et al, 2017;Reed et al, 2017;Jennings et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The observation that tangle‐web spiders have higher C content than their prey provides support to the hypothesis that predators may suffer from C (i.e., energy) limitation (Wilder et al., 2013). Recent empirical research suggests that energy limitation may be common for some predatory species such as ants, beetles, and spiders (Grover, Kay, Monson, Marsh, & Holway, 2007; Kohl, Coogan, & Raubenheimer, 2015; Noreika, Madsen, Jensen, & Toft, 2016; Wilder et al., 2013; Wiggins & Wilder, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…In Jensen et al (2011), prey containing high levels of protein shortened juvenile development time and increased body size in the wolf spider Pardosa amentata although the juveniles were observed for only a few instars. In the jumping spider Phidippus audax, however, Wiggins and Wilder (2018) found that high-lipid prey was associated with larger body size (tibia/patella length and posterior-lateral eye width) and heavier weight. In our experiments, the positive effects of mother diet on juvenile growth were mediated by some substances in midges after a single feeding.…”
Section: Discussionmentioning
confidence: 94%